Circular RNA circVAPA contributes to non-small-cell lung cancer progression via miR-342-3p-dependent regulation of ZEB2 - Xiaoyang Liu (BMC, 2021)
Abstract Background Accumulating evidence demonstrated that circular RNAs (circRNAs) play pivotal regulatory roles in the pathology of cancers. Disclosing the roles and molecular mechanisms of circRNAs in tumorigenesis and development is essential to identify novel diagnostic and therapeutic targets. In this study, we explored the role of circVAPA in non-small-cell lung cancer (NSCLC) progression and its associated mechanism. Methods The expression level of RNA was analyzed by real-time quantitative polymerase chain reaction (RT-qPCR). Cell proliferation was assessed by MTT assay and colony-forming assay. Cell apoptosis was analyzed by flow cytometry. Cell migration and invasion were assessed by transwell assays. Dual-luciferase reporter, RNA pull-down, and RNA immunoprecipitation (RIP) assays were used to test the intermolecular interactions. The role of circVAPA was assessed in vivo. And xenograft tumor tissues were analyzed by immunohistochemistry (IHC) staining. Results CircVAPA expression was upregulated in NSCLC tissues and cell lines, and a high level of circVAPA was associated with a poor prognosis of NSCLC patients. CircVAPA silencing suppressed the proliferation, migration, and invasion and induced the apoptosis of NSCLC cells. CircVAPA served as a molecular sponge for microRNA-342-3p (miR-342-3p). miR-342-3p interference largely reversed circVAPA knockdown-mediated anti-tumor effects in NSCLC cells. Zinc finger E-box-binding homeobox 2 (ZEB2) was a target of miR-342-3p, and miR-342-3p overexpression suppressed the malignant behaviors of NSCLC cells largely by downregulating ZEB2. CircVAPA silence repressed xenograft tumor growth in vivo, and IHC assay confirmed that circVAPA silence restrained the proliferation and metastasis but induced the apoptosis of NSCLC cells in vivo. Conclusion CircVAPA contributes to the progression of NSCLC by binding to miR-342-3p to upregulate ZEB2. CircVAPA/miR-342-3p/ZEB2 axis might be a novel potential target for NSCLC treatment.